Evaluation of Ecotourism Potential in Jatigede District, Sumedang Regency - Raynaldi, Rizki; Andari, Rini (Graduate School, Universitas Brawijaya, 2024)
Stakeholders, including as governments, local communities, businesses, and tourists, participate an important part in promoting and supporting the implementation of ecotourism initiatives. Jatigede District, being one of the regional government's development priority areas, has significant potential for the development of ecotourism. Examining the region's potential, economy, and social conditions is an aspect of this research. To collect field data, interviews were conducted with the primary stakeholders who participated in the tourism development of the Jatigede District. To effectively support the development of ecotourism areas in Jatigede District, several strategies can be implemented. These strategies include improving stakeholder communication, upgrading infrastructure, applying effective promotion strategies, and investing in human resources.